الكشف عن التلوّث بفطور التخزين والأفلاتوكسينات في كسبة فول الصويا (Latakia University Journal -Biological Sciences Series, 2019)
تم عزل/16/جنساً فطرياً من11//عينة كسبة فول صويا محليّة ومستوردة، وذلك على مستنبتي PDA,MSA وكان عدد المستعمرات الفطريّة أعلى على مستنبتPDA حيث وصل في غرام كسبة بالمتوسط إلى/209.7X105/، ومن أهمّ الأجناس التي تم عزلها: Cladosporium، Aspergillus Alternaria،Penicillium ،Rhizopus ،Scopulariopsis ، Absidia، Mucor، ووصلت نسبة تلوّث العينّات إلى 100% بجنسي  Aspergillus وCladosporium، وكان أكثر الأنواع تردداً في كلّ العيّنات vuill Aspergillus fumigatus. تراوحت نسبة المحتوى الرطوبيّ لعينات الكسبة بين9.6-14.6%، ولم يظهر المحتوى الرطوبيّ للعيّنات علاقة واضحة بتركيز الأفلاتوكسينات الكلية(B1,B2,G1,G2) فيها، ووجد بأنّ كلّ العينات كانت ملوثة بالأفلاتوكسينات الكلية وبلغ أعلى تركيز لها /16  PPB/. 16 species have been obtained from 11 samples of local and imported soybean meal. The isolation is on PDA, MSA media. The average number of fungal colonies is higher on PDA, where it notches 209.7x10 5 colony/g. The most important isolated species are: Cladosporium, Aspergillus, Alternaria, Penicillium, Rhizopus Scopulariopsis, Absidia, and Mucor. The contamination percentage of the samples concerned is 100% with Aspergillus, Cladosporium, and the most prevalent species is Aspergillus fumigatus vuill. The moisture content of samples ranges between 9.6 and 14.6% and does not show any obvious relationship with the Aflatoxins concentration. All samples are contaminated with Aflatoxins, and the highest percentage is 16 ppb.